Edgar the Ready: A Tale of the Third Edward's Reign - Shervill, W. P.; Sheldon, Charles Mills, 1866-1928 (Salt Lake City, UT : Project Gutenberg, 2015)
"Edgar the Ready: A Tale of the Third Edward's Reign" by W. P. Shervill is a historical novel written in the early 20th century. The book is set during the reign of King Edward III and follows the journey of a young aspiring knight named Edgar Wintour. As the narrative unfolds, readers can expect the trials and tribulations faced by Edgar, weaving themes of bravery, chivalry, and the harsh realities of medieval warfare. The opening of the tale introduces Edgar$1 (Bs companion, Matthew, as they embark on a perilous journey to Wolsingham Castle. Their path is fraught with unexpected dangers, including an ambush by robbers that reveals Edgar$1 (Bs quick thinking and courage. When they later stop at a farmhouse for the night, they find themselves in yet another perilous situation, showcasing Edgar$1 (Bs growth and moral character. This prologue sets the stage for Edgar's adventures as he strives to honor his father's legacy, face the complexities of knighthood, and navigate the political landscape of his time. (This is an automatically generated summary.)s
Release date is 2015-06-25
Produced by Al Haines
Keywords: Great Britain -- History -- Edward III, 1327-1377 -- Juvenile fiction